Caracterização do crescimento, desenvolvimento e pós-colheita da abóbora cv. mini-Jack - Graça, Genilza Almeida da (2022)
Based on knowledge about the physiological changes that occur during cultivation of pumpkin fruits, post-harvest losses can be reduced and shelf life extended. The purpose of this study was to characterize growth and development of pumpkin (cv. Mini-Jack) and to describe the postharvest performance of fruits stored in a modified environment cooled to 5 ºC. To measure growth and development, the fruits were harvested at 0, 5, 10, 15 and 20 days after anthesis (DAA) and the following characteristics evaluated: fruit height, total diameter, internal concavity and weight; skin color, pulp firmness, pulp and peel thickness, respiratory rate, pH, solid acids, total soluble solids (TSS) in peel, carotene in pulp and peel, and reducing, nonreducing and total sugars in the fruit pulp. The fruit response to 18 storage treatments was assessed: unpackaged fruits stored at room temperature (28°C) (control), fruits in a modified environment (covered with PVC film) and cooled to 5 °C, and unpackaged fruits cooled to 5 °C. The stored fruits were evaluated weekly for 35 days. A development pattern represented by a single sigmoid curve was observed. The respiratory rate was high at the beginning of development (0 - 5 DAA) and decreased and stabilized 10 DAA, which is characteristic of nonclimacteric fruits. During fruit growth and development, the levels of total sugars, TSS and carotene increased up to 10 DAA. In all storage treatments, fruit weight decreased during storage. However, when stored in a modified environment cooled to 5ºC, weight loss was reduced. No significant variation in total sugars was observed, especially in fruits maintained at room temperature. The firmness of cooled and packaged fruits was greater than in the other treatments throughout the evaluations. Therefore, the ideal point for harvesting pumpkin cv. Mini-Jack was inferred to be at 15 DAA and refrigeration at 5ºC was considered efficient to reduce losses and maintain the quality of the stored fruits.